1975
DOI: 10.1136/ard.34.5.379
|View full text |Cite
|
Sign up to set email alerts
|

New Haven survey of joint diseases. XVII. Relationship between some systemic characteristics and osteoarthrosis in a general population.

Abstract: Acheson, R. M., and Collart, A. B. (1975). Annals of the Rheumatic Diseases, 34, 379-387. New Haven survey of joint diseases. XVII. Relationship between some systemic characteristics and osteoarthrosis in a general population. In a survey of the general population the presence or absence ofosteoarthrosis of the hand was determined radiologically in 685 adults (300 males and 385 females). Of these, 261 (124 males and 137 females), chosen randomly, were given a complete clinical examination of the musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
0
2

Year Published

1992
1992
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(44 citation statements)
references
References 17 publications
4
38
0
2
Order By: Relevance
“…In contrast, Sun et al [6] specifically studied the interaction between serum urate levels and OA and observed an increase in generalized OA in patients with hyperuricemia, although only when the hip joint was involved. These results are in concert with those of Acheson et al [7], who found a strong correlation between serum UA levels and generalized OA in a previous study. In both studies, the authors postulated that the association between hyperuricemia and OA might be explained by a shared common risk factor (eg, increased risk for avascular necrosis in the subchondral bone of the hip related to hyperuricemia, or a related metabolic or insulin resistance syndrome) rather than any direct effect of serum urate on the affected joints.…”
Section: Hyperuricemia and Osteoarthritissupporting
confidence: 92%
“…In contrast, Sun et al [6] specifically studied the interaction between serum urate levels and OA and observed an increase in generalized OA in patients with hyperuricemia, although only when the hip joint was involved. These results are in concert with those of Acheson et al [7], who found a strong correlation between serum UA levels and generalized OA in a previous study. In both studies, the authors postulated that the association between hyperuricemia and OA might be explained by a shared common risk factor (eg, increased risk for avascular necrosis in the subchondral bone of the hip related to hyperuricemia, or a related metabolic or insulin resistance syndrome) rather than any direct effect of serum urate on the affected joints.…”
Section: Hyperuricemia and Osteoarthritissupporting
confidence: 92%
“…In the present study, with wider diagnostic criteria for radiographic osteoarthritis, similar results were obtained. Sex differences in the prevalence of radiographic osteoarthritis in both hand and knee joints have, however, been found in a number of studies, and a higher prevalence of osteoarthritis has been reported in women after the age of 55 (1)(2)(3)(4)(5)(6)(7)(8)(9)(22)(23)(24). These studies do, however, not include age-specific groups of individuals over the age of 75.…”
Section: Discussionmentioning
confidence: 80%
“…However, of the three-knee, hip, and hand OA-the evidence for OA of the hand is the most equivocal. Older studies have found an association between OA of the interphalangeal joints and overweight/obesity in males [51] and both males and females [52]. In one large cross-sectional study of the general population, obesity was found to be strongly associated with OA of the knees and the carpometacarpal joint and weakly associated with OA of the interphalangeal joints [44].…”
Section: Osteoarthritismentioning
confidence: 99%